Unconjugated hyperbilirubinemia in the patients with celiac trunk compression syndrome - A. M. Ignashov; D. V. Kachalov; M. M. Antonov; V. E. Perley; A. U. Gichkin; T. M. Tabakova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The level of the total, conjugated and unconjugated bilirubin has been assessed after celiac trunk decompression in 621 patients with celiac trunk compression syndrome. Relatively mild, mainly unconjugated hyperbilirubinemia has been found in 23.4 % of the young patients predominantly. The main values of the celiac trunk duplex scanning have been hemodynamically significant. Normalization of bilirubin and its fractions values was seen in most of the patients in the early postoperative course after surgical celiac trunk decompression. The results show the effect of the celiac trunk stenosis and decrease in the liver blood flow on the possible development of unconjugated hyperbilirubinemia in the patients with this artery compression syndrome.